Validation of a simple extraction procedure for bisphenol A identification from human plasma - Wiraagni, Idha Arfianti; Mohd, Mustafa Ali; Abd Rashid, Rusdi; Haron, Didi Erwandi Mohamad (Public Library of Science, 2019)
The general population is exposed to bisphenol A (BPA) orally, parenterally, transdermally, and environmentally as a result of the use of BPA in food packaging, plastics, and personal care products. The majority of the population nowadays (91–99%) has detectable levels of BPA inside their body. In this study, we successfully performed an inexpensive, rapid, and simple protein precipitation procedure for extraction of BPA from human plasma, followed by analysis by LC-MS/MS. This method was specifically developed for handling large numbers of samples with minimum cost and volume of sample. The developed method was accurate, precise, and reproducible for quantification of BPA from human plasma samples in the concentration range of 10–2000 ng/mL. The method was performed on samples from 150 healthy volunteers who were enrolled in the study. The mean of observed BPA level was 2.22 ± 9.91 ng/mL. Higher BPA levels were observed for females compare to that of males (p-value = 0.002), the BPA levels were higher in participants 33 years of age and older compared to those less than 33 years of age (p-value = 0.000), then the BPA levels higher in subjects with tap water as source of drinking (p-value = 0.005). This method may be valuable for general risk assessment of BPA for a large and varied population because of its efficiency and economical aspects. © 2019 Wiraagni et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.